The Effect of Bull Age and Ejaculation Frequency on Quality of Aceh Bull Spermatozoa - Dini Melita; Dasrul Dasrul; Mulyadi Adam (Universitas Syiah Kuala, 2014)
The purpose of this research was find out the effect of age and ejaculation frequency on quality of Aceh bull spermatozoa.. This research was conducted at Frozen Semen Prossesing Laboratorium, Saree, Aceh Besar from Januari to April 2013. Six healthy aceh bulls were divided into two groups of age, those were 3.0-4.0 years old; and 4.0-5.0 years old. Three numbers of bull at each group were assumed as the replication. Semen was collected once a week using artificial vagina and collected until third semen ejaculation. After collecting, volume, pH, color, consistency, concentration, motility, mortality, and abnormality of spermatozoa were immediately measured. This data was analyzed by analysis of variance (ANOVA) two-way pattern, followed by Duncant test. The result showed that the evaluation of bull semen at 3.0-4.0 years old and 4.0-5.0 years old affect significantly (P0.05) on semen volume and spermatozoa concentration and had no contribute significantly on motility, mortality and abnormality of spermatozoa,while ejaculation frequency effect significantly (P0.05) on semen volume, concentration, and abnormality spermatozoa, but had no effect significantly on motility and mortality (P0.05). It is concluded that aged and ejaculation frequency effect significantly on quality of aceh bull fresh spermatozoa.Key words: ejaculation frequency, quality of spermatozoa, aceh bull, age